2004
DOI: 10.1310/3hl3-hhbd-wklr-xell
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Virological Response to Atazanavir in Protease Inhibitor-Experienced Patients

Abstract: ATV is relatively safe and provides significant virological response in PI-experienced patients, mainly among those with a low number of protease resistance mutations. The GIQ predicts accurately the virological response in patients receiving ATV. Hyperbilirubinemia is associated with higher ATV plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…About 20%-50% of patients exposed to ATV may develop hyperbilirubinemia that can be severe in about 6% of cases [57]. Several studies have shown the correlation between ATV plasma levels and the risk of bilirubin elevations [47,48,58]. Polymorphisms at the UGT1A1 gene have been related with a diminished activity of the enzyme, affecting the metabolism of bilirubin.…”
Section: Pharmacogenetics Of Atazanavirmentioning
confidence: 99%
“…About 20%-50% of patients exposed to ATV may develop hyperbilirubinemia that can be severe in about 6% of cases [57]. Several studies have shown the correlation between ATV plasma levels and the risk of bilirubin elevations [47,48,58]. Polymorphisms at the UGT1A1 gene have been related with a diminished activity of the enzyme, affecting the metabolism of bilirubin.…”
Section: Pharmacogenetics Of Atazanavirmentioning
confidence: 99%
“…2 In addition, data from PI-experienced patients revealed that the median number of PI-associated resistance mutations was lower in patients showing virological response than in non-responders. 9 As with other PIs, failure of ATV is often rather better explained by lack of potency than by the acquisition of primary resistance mutations, especially in patients without previous PI failure. 10 In PI-experienced patients, the genotypic inhibitory quotient (GIQ) has been proven to be a good predictor of virological response to ATV, as it integrates both resistance mutations and drug plasma exposure.…”
Section: Drug Resistancementioning
confidence: 99%
“…10 In PI-experienced patients, the genotypic inhibitory quotient (GIQ) has been proven to be a good predictor of virological response to ATV, as it integrates both resistance mutations and drug plasma exposure. 9 …”
Section: Drug Resistancementioning
confidence: 99%
“…54 A direct corelation between ATV plasma concentrations and bilirubin levels has also been noticed by others. 55 Most PI are subject to P-gp transportation. Polymorphisms at the MDR1 gene that affect P-gp activity may be the genetic underlying mechanism for significant inter-individual variations in PI plasma levels.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…These authors observed a reduction in virus production when P-gp was overexpressed at the surface of a continuous CD4 þ human T-leukemic cell line infected with HIV-1. 55 This reduction in viral infectivity occurred both during the fusion of viral and plasma membranes and at subsequent steps in the HIV-1 cycle. However, Ifergan et al 79 compared infected and non-infected Caucasian individuals highly exposed to HIV and they observed no differences in the distribution of P-gp genotypes between both groups, suggesting that P-gp expression does not play a major role in the susceptibility to HIV infection.…”
Section: Pharmacogenetics and Efficacy Of Antiretroviral Drugsmentioning
confidence: 99%